Management of postmenopausal women: Collège National des Gynécologues et Obstétriciens Français (CNGOF) and Groupe d'Etude sur la Ménopause et le Vieillissement (GEMVi) Clinical Practice Guidelines. (September 2022) - Trémollieres, F.A.; Chabbert-Buffet, N.; Plu-Bureau, G.; Rousset-Jablonski, C.; Lecerf, J.M.; Duclos, M.; Pouilles, J.M.; Gosset, A.; Boutet, G.; Hocke, C.; Maris, E.; Hugon-Rodin, J.; et al.
Highlights: The focus of the first menopause consultation is to address and provide answers to women's questions about menopause. At menopause, improving lifestyle and nutrition, avoiding risk factors (notably smoking), and promoting physical activity could help limit the long-term impact of estrogen deficiency. In women with moderate to severe vasomotor symptoms and in the absence of contraindications, it is recommended to prescribe menopausal hormone therapy (MHT) as first-line treatment. For the management of genitourinary syndrome of menopause, vaginal treatment is recommended as first-line treatment. In early postmenopausal women at low to moderate risk of fracture, it is recommended that MHT be proposed as first-line treatment to prevent osteoporosis. To limit the excess risk of breast cancer associated with MHT, it is recommended that estradiol be combined with progesterone or dydrogesterone. Current data do not allow the recommendation of an optimal duration of MHT, which must take into account its initial indication and its benefit–risk balance. Abstract: Aim: The aim of these recommendations is to set forth an individualized approach to the management of early postmenopausal women (i.e., within the first 10 years after natural menopause) covering all aspects of lifestyle and therapeutic management, with or without menopause hormone therapy (MHT). Materials and methods: Literature review and consensus of French expert opinion. Recommendations were graded according to the HAS methodology and levels of evidence derived from the international literature, except when there was no good-quality evidence. Summary recommendations: The beginning of menopause is an ideal time for each woman to evaluate her health status by assessing her bone, cardiovascular, and cancer-related risk factors that may be amplified by postmenopausal estrogen deficiency and by reviewing her lifestyle habits. Improving lifestyle, including nutrition and physical activity, and avoiding risk factors (notably smoking), should be recommended to all women. MHT remains the most effective treatment for vasomotor symptoms but it could be also recommended as first-line treatment for the prevention of osteoporosis in early postmenopausal women at low to moderate risk for fracture. The risks of MHT differ depending on its type, dose, duration of use, route of administration, timing of initiation, and whether a progestogen is used. There is reasonable evidence that using transdermal estradiol in association with micronized progesterone or dydrogesterone may limit both the venous thromboembolic risk associated with oral estrogens and the risk of breast cancer associated with synthetic progestins. Treatment should be individualized to each woman, by using the best available evidence to maximize benefits and minimize risks, with periodic reevaluation of its benefit–risk balance. For bothersome genitourinary syndrome of menopause (GSM) symptoms, vaginal treatment with lubricants and moisturizers is recommended as first-line treatment together with low-dose vaginal estrogen therapy, depending on the clinical course. No recommendation of an optimal duration of MHT can be made, but it must take into consideration the initial indication for MHT as well as each woman's benefit–risk balance. Management of gynecological side-effects of MHT is also examined. These recommendations are endorsed by the Groupe d'Etude sur la Ménopause et le Vieillissement hormonal (GEMVI) and the Collège National des Gynécologues-Obstétriciens Français (CNGOF).